Academic Supervision of School Principals and Teacher Performance: A Literature Review - Sunaryo, Yohanes Sunaryo (Universitas Pendidikan Indonesia, 2020)
The principal must be able to manage the performance of teachers in his school. In carrying out their responsibilities in managing performance, school principals contribute to improving overall teacher performance in an effort to get better results. The research will be conducted under the title Academic Supervision of School Principals and Teacher Performance. The aim is to find out the extent of the influence of the principal's academic supervision on teacher performance. Education policy must be supported by education practitioners who are at the forefront, namely teachers through their interactions in education. The involvement of all components of education (teachers, principals, communities, and school committees) through good planning and realizing the educational programs that are launched is very necessary. Academic supervision conducted by the Principal has a positive and significant effect on changes in teacher performance. Teacher performance can be improved if the academic supervision of the principal in the form of leadership and supervision is improved.